Aspirin Inhibits Carcinogenesis of Intestinal Mucosal Cells in UC Mice Through Inhibiting IL-6/JAK/STAT3 Signaling Pathway and Modulating Apoptosis and Proliferation - Chen, Yingying; Sun, Liying; Li, Dongyue; Yin, Xunhai; Shang, Guoyin; Diao, Tiantian; Shi, Lijun (Turkish Journal of Gastroenterology, 2022)
Background: Colorectal cancer is related to ulcerative colitis. This study aimed to investigate the effects of aspirin on non-specific inflammation developing into cancer. Methods: Ulcerative colitis model was generated by administrating azoxymethane/dextran sulfate sodium to mice. Weight, tumor size/ amount, and intestinal mucositis scores were analyzed. Inflammatory cell infiltration and atypical hyperplasia were determined with hematoxylin–eosin staining. Immunohistochemical assay was used to detect the proliferating cell nuclear antigen. Interleukin-6 and interleukin-10 were detected using enzyme-linked immunosorbent assay. Signal transducer and activator of transcription 3, phosphorylated-STAT3, cyclin D1, and suppressor of cytokine signaling 3 were examined with western blotting. Results: Aspirin remarkably decreased tumor size/amount compared to those of the ulcerative colitis model group (P < .05). Interleukin-6 was increased and interleukin-10 was decreased in mice of ulcerative colitis model group compared with the control group (P < .05). Aspirin markedly reduced interleukin-6 and enhanced interleukin-10 compared to the ulcerative colitis model group (P < .05) induced Azoxymethane/dextran sulfate sodium inflammation (3 weeks) and atypical hyperplasia (8 weeks). Aspirin predominantly inhibited the “inflammation–atypical hyperplasia–cancer” process and alleviated inflammatory cell infiltration of mice in the ulcerative colitis model group. Aspirin promoted apoptosis and alleviated proliferating cell nuclear antigen of atypical hyperplastic intestinal mucosal cells at 8 weeks post-modeling. The expression of phosphorylated-STAT3, signal transducer and activator of transcription 3, cyclin D1, and suppressor of cytokine signaling 3 was significantly increased in mice of ulcerative colitis model group compared to the control group (P < .05). Aspirin remarkably decreased phosphorylated-STAT3, signal transducer and activator of transcription, and cyclin D1 expression compared with ulcerative colitis model group (P < .05). Conclusion: Aspirin inhibited carcinogenesis of intestinal mucosal cells in the ulcerative colitis model by inhibiting the interleukin-6/ Janus kinase/signal transducer and activator of transcription 3 signaling pathway and promoted apoptosis, thereby suppressing proliferation Cite this article as: Chen Y, Sun L, Li D, et al. Aspirin inhibits carcinogenesis of intestinal mucosal cells in UC mice through inhibiting IL-6/JAK/STAT3 signaling pathway and modulating apoptosis and proliferation. Turk J Gastroenterol. 2022;33(9):731-742.